Rapamycin reduces DNA damage of in vitro matured oocytes by promoting Rad51-mediated homologous recombination - Qiyu Yang; Ying Chen; Jiayu Huang; Junying Tang; Lixia Zhu; Jingyu Li; Chao Tong (Reproductive Biology and Endocrinology)
Abstract Background The quality of in vitro matured (IVM) oocytes remains inferior to that of in vivo matured oocytes, likely due to DNA damage induced by the in vitro environment. Although rapamycin has been shown to improve the developmental competence of IVM oocytes by reducing DNA double-strand breaks (DSBs), the underlying mechanisms remain unclear. Methods Immature oocytes from 6 ~ 8-week-old ICR female mice were subjected to IVM with or without rapamycin. After 14 ~ 16 h, the maturation rate, DNA DSB levels, and subsequent developmental competence of IVM oocytes were assessed. The homologous recombination (HR) and non-homologous end joining (NHEJ) pathways were selectively inhibited using RAD51 and DNA-PK inhibitors, respectively, to elucidate the predominant DNA damage repair pathway during IVM and investigate the effects of rapamycin on this process. Results Embryos derived from the rapamycin-treated group exhibited significantly higher 2PN and cleavage rates compared to the control group. MII oocytes cultured with rapamycin showed reduced γH2AX immunofluorescence intensity, indicating lower DNA damage levels. Additionally, the expression levels of RAD51 and DNAPK were elevated in rapamycin-treated oocytes. Inhibition of RAD51 significantly reduced the maturation rate and increased DNA damage levels, whereas DNAPK inhibition had no effect on oocyte development or quality. Importantly, the beneficial effects of rapamycin on IVM oocytes were diminished under RAD51 inhibition. Conclusion Rapamycin improves the developmental competence of IVM oocytes by enhancing the RAD51-mediated HR pathway, thereby enhancing DNA stability.